STUDI PERBANDINGAN DINAMIKA PERMAINAN PADEL DAN TENIS LAPANGAN DALAM PERSPEKTIF OLAHRAGA RAKET - Ali Usman Fahreza Siregar; Grace Theresia Zebua; Imanuel Junjungan Soaloan Hutagalung; Irlansyah Telaumbanua; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Racket sports consist of various types of games, including padel and lawn tennis. The two are often considered similar because both use rackets and balls, but there are fundamental differences in technique, strategy, court size, and physical demands of each game. This study aims to analyze the differences in the dynamics of padel and lawn tennis through a literature review of both international and national sources. The research method used is a literature study by examining scientific documents, theoretical books, and popular articles related to both sports. The research subjects consist of secondary data in the form of literature on padel and lawn tennis, taken from international and national journals. Data analysis was carried out using a descriptive-comparative approach, describing the characteristics of each sport and then comparing them based on technique, strategy, physiological aspects, and facilities. The research stages include determining the focus of the study, collecting relevant literature, grouping data, conducting descriptive analysis, and drawing conclusions. The findings show that padel tends to focus on short rallies, the use of walls during play, and intense partner coordination, while lawn tennis emphasizes ball speed, shot power, and strategies in open courts. This study is expected to provide deeper insights for coaches, athletes, and academics in developing learning and training models for racket sports.